Cognition in Recent Suicide Attempts: Altered Executive Function - Fernández-Sevillano, Jessica; Alberich, Susana; Zorrilla, Iñaki; González-Ortega, Itxaso; López, María Purificación; Pérez, Víctor; Vieta, Eduard; González-Pinto, Ana; Saíz, Pilar (Frontiers in Psychiatry, 2021)
Background: Neuropsychological alterations can lead to inaccurate perception, interpretation and response to environmental information, which could be a risk factor for suicide. Methods: 96 subjects were recruited from the Psychiatry Department of the Araba University Hospital-Santiago including 20 patients with a recent attempt and diagnosis of Major Depressive Disorder (MDD) according to DSM-V, 33 MDD patients with history of attempted suicide, 23 non-attempter MDD patients and 20 healthy controls. All participants underwent a clinical interview and neuropsychological assessment on the following cognitive domains: working memory, processing speed, decision-making, executive function and attention. Backward multiple regressions were performed adjusting for significant confounding variables. For group comparisons ANOVA test and Bonferroni post hoc test were performed with p<0.05 significance level. Results: Patients groups did not differ regarding severity of depression and stressful events in the last 6 months. In comparison to healthy controls, depressed patients with lifetime suicide attempts had more general trauma (p=0.003), emotional abuse (p=0.003), emotional negligence (p=0.006) and physical negligence (p=0.009) and depressed patients with recent suicide attempts had experience more child sexual abuse (p=0.038). Regarding neuropsychological assessment, all patient groups performed significantly worse than healthy controls in processing speed, decision making and attention. Comparisons between patient groups indicated that recent suicide attempters had a poorer performance on executive function in comparison to both depressed lifetime attempters and depressed non-attempters (B=0.296, p=0.019 and B=0.301, p=0.028 respectively). Besides, women with recent attempts had slightly better scores on executive function than males. Regarding the rest of cognitive domains, there were no significant differences between groups. Conclusion: Executive function performance is altered in recent suicide attempts. As impaired executive function can be risk factor for suicide, preventive interventions on suicide should focus in its assessment and rehabilitation.